Police Crime Across the Life Course: An Exploratory Study of Arrested Officers Who Reoffend - Stinson, Philip M (2019)
The purpose of this study is to improve policing and inform the public about police crime and patterns of repeat or habitual police crime offenders. The study identified 10,287 arrest cases involving 8,495 individual nonfederal sworn law enforcement officers, each of whom were arrested during the decade 2005-2014. Of these, 505 officers (5.94%) were arrested more than once in the study years and account for 1,343 (13.06%) of the arrest cases in our database. This poster presents data on the criminal arrest cases and the officers who have been arrested multiple times while employed by a state or local law enforcement agency within the United States. Cases were identified using 48 automated Google Alerts that constantly crawl the Google News search engine. Data sources were triangulated and court records obtained when available. Exploratory analysis discovers patterns of arrested officer and victims demographics, details of the crimes, final adverse employment outcomes, and criminal case dispositions. Additionally, the relationships between criminal case disposition and other variables of interest are explored. Presented at the American Society of Criminology Annual Meeting in San Francisco, CA